STRATEGIC MANAGEMENT IN ENSURING ECONOMIC AND FINANCIAL STABILITY - Akramova Aziza Abduvohidovna (Journals Park Publishing, 2024)
This article presents the stages of strategic management in ensuring economic and financial stability, the purpose of strategic analysis. The stages of strategic selection and implementation of 5P strategy and several models of their application are highlighted.
Keywords: Strategic management, strategic analysis, strategic choice, strategy implementation and management, 5P strategy, behavior model strategy, method or tactical way.